A short history of almond cultivation in Apulia (southern Italy): Its rise and decline - Godini A. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
According to Cato (the Censor) and Virgil, almonds were grown and known in Italy in the first century BC. In Apulia, almond paper and soft-shell varieties were grown and known in the first century AD. In Apulia region the crop achieved an impressive development during the sixteenth (L. Alberti, 1577) and eighteenth (De Salis Marschlins, 1789) centuries. The almond industry attained its absolute maximum extension between the two World Wars when the crop replaced wine and table grapes, seriously damaged following the phyloxera invasion. The lack of competition in Europe made the Apulian almond industry very profitable, but did not stimulate the improvement of the standard cultural methods consisting in growing almonds under rainfed conditions on shallow, poor and arid soils. The very low unit yields were unable to withstand the increasing competition mainly by the USA almond industry, which expanded tremendously starting from the 1960s.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)